2006
DOI: 10.1111/j.1745-9125.2006.00052.x
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Test of the Effects of Parenting and the Stability of Self-Control: Negative Evidence for the General Theory of Crime*

Abstract: This study investigates two core propositions of Gottfredson and Hirschi's (1990) general theory of crime. Using longitudinal data collected on approximately 750 African American children and their primary caregivers, we first examine whether self‐control fully mediates the effect of parenting on delinquency. Consistent with the general theory, we find that low self‐control is positively associated with involvement in delinquency. Counter to Gottfredson and Hirschi's proposition, we find that self‐control only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
304
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(340 citation statements)
references
References 75 publications
32
304
2
2
Order By: Relevance
“…Research findings also indicated that the role of social economic status in discriminatory attitudes, in consistent with the previous studies (Simons, Simons, & Burt, 2006), there was not any statistical group differences. However, students with high social economic status had more discriminatory attitudes than middle and low group.…”
Section: Discussionsupporting
confidence: 80%
“…Research findings also indicated that the role of social economic status in discriminatory attitudes, in consistent with the previous studies (Simons, Simons, & Burt, 2006), there was not any statistical group differences. However, students with high social economic status had more discriminatory attitudes than middle and low group.…”
Section: Discussionsupporting
confidence: 80%
“…Gottfredson and Hirschi (1990) stated that self-control is largely determined by parenting practices during early childhood and stable around the ages of 8 to 10. Burt et al (2006) found, however, that self-control is not as stable after the age of 10 as Gottfredson and Hirschi assumed. They furthermore found substantial effects of parenting on changes in self-control after the age of 10.…”
Section: Sex Differences In Indirect Pathways From Parenting To Delinmentioning
confidence: 65%
“…Although early prevention is important , promising research does suggests that self-control is plastic and is susceptible to change in later stages of one's life-course too (Burt et al, 2006;Moffitt et al, 2011;Roberts, Walton, & Viecthbauer, 2006). As such, both unique and universal prevention and intervention efforts will be important to develop for targeting developmentally sensitive periods that teaches individuals to make informed decisions before acting; seriously consider how their actions affect others; and more generally teach them to think about the personal consequences of their own behavior.…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…of self-control over time (Burt et al, 2006;Hay & Forrest, 2006). Criminologists have investigated correlates and predictors of self-control that provide insights into what factors should be focused on for intervention purposes.…”
Section: Implications For Policy and Practicementioning
confidence: 99%